State labor legislation enacted in 2000. - Nelson, Richard R. (Monthly Labor Review, 2001)
The writer discusses significant state labor legislation passed in 2000. Activity was focused in the traditional areas of minimum wage protection, regulation of child labor, and on bans on employment discrimination. Trends continued from previous years, with additional states awarding employers immunity from civil liability for disclosure of work performance information and authorizing reciprocal agreements for the collection of wage claims. New laws enacted address workplace harassment and violence and protect whistleblowers. A first in-the-country law enacted places restrictions on mandatory overtime, and for the first time, an indexed state minimum wage rate took effect.